Association of vitamin D3, VDR gene polymorphisms, and LL-37 with a clinical form of Chagas Disease - Oliveira Junior, Luiz Roberto De; Carvalho, Thaysa Buss; Santos, Rodrigo Mattos Dos; Costa, Érika Alessandra Pellison Nunes Da; Pereira, Paulo Câmara Marques; Kurokawa, Cilmery Suemi (Sociedade Brasileira de Medicina Tropical - SBMT, 2019)
AbstractINTRODUCTION:Chagas disease (CD) is an important public health problem in Brazil and worldwide. Aging and obesity are important matters in patients with CD, as is hypovitaminosis D3, which can decrease the quality of life of these patients. Immunomodulation mediated by vitamin D3, especially the production of antimicrobial peptides such as cathelicidin LL-37, might be related to the severity and symptoms of CD. This study aimed to determine the serum levels of vitamin D and LL-37 and VDR gene polymorphisms in patients with chronic CD.METHODS:This study included male patients with cardiac and indeterminate clinical forms of CD. Clinical, anthropometric, and blood parameters were obtained. Serum levels of 25(OH)D3 and LL-37 were determined by chemiluminescence and enzyme-linked immunosorbent assay respectively. Fok (rs731236), Bsm (rs1544410), Apa (rs7975232), and Taq (rs731236) polymorphisms of the VDR gene were investigated by PCR-RFLP.RESULTS:Sixty-four patients were included in the study: 18 of the cardiac form and 46 of the indeterminate form. No differences in age, ethnicity, BMI, arterial hypertension, diabetes mellitus, or dyslipidemias were observed between groups. However, the serum levels of 25(OH)D3, but not of LL-37, were lower in the cardiac form group. The association among polymorphisms, vitamin D, and clinical form was not significant.CONCLUSIONS:Decreased levels of vitamin D suggest an association with the cardiac form of CD. Studies investigating the roles of vitamin D and LL-37 in the immune response and their associations with VDR polymorphisms and disease susceptibility are necessary.
Keywords: Chagas Disease; Vitamin D3; LL-37